The impact of the use of technological resources on the performance daily activities and the satisfaction of the mother having child with severe cerebral palsy - Barbosa, Rafaela Brigoni; Zafani, Mariana Dutra; Baleotti, Luciana Ramos (Revista de Terapia Ocupacional da Universidade de São Paulo, 2020)
The general objective of this study was to identify how the mother of a three-year-old child with severe spastic quadriplegic cerebral palsy perceives the technological resources used by her child to perform daily functional tasks. The specific objectives were: list and indicate how often, according to the Pediatric Assessment Inventory (PEDI), the child used modifications; identify the level of satisfaction of the mother regarding such modifications, the difficulties to apply them and the need for guidelines. For data collections, we used the PEDI and a semi-structured interview script. The results suggest that the mother was pleased with the technological resources used by her son and well advised about how to apply them. Among the negative aspects influencing the usability of such resources, this work found public places lacking wheelchair accessibility and low family income. While the results of this study reinforce the need to engage the family in the process of choosing the technological resources, they also show how relevant it is to have a professional who may consistently analyze the environmental context in which such resources are found and so allow for an easier use and indeed promote a better quality of life for the disabled person and their family members.